THE CRUCIAL ROLE OF PARENTS IN INSTILLING A THRIFTY LIFESTYLE AMONG CHILDREN IN KRANGGAN WETAN WIROGUNAN VILLAGE, KARTASURA, SUKOHARJO - Suyahman, Suyahman (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
This research aims to describe the role of parents in cultivating a thrifty lifestyle among their children in Kranggan Wetan Village, Wirogunan, Kartasura, Sukoharjo. The research adopts a qualitative approach with a descriptive design. The subjects of the study are parents and their children, with the object of the study being a thrifty lifestyle. Data collection methods include observation, interviews, and documentation. Data validity is ensured through source and method triangulation. The research findings, based on observations conducted from December 1 to December 30, 2023, reveal that parents employ various methods to instill a thrifty character in their children. These include limiting pocket money, monitoring their children's spending, preparing snacks at home, regulating screen time, managing sleep patterns, and controlling their children's eating and resting habits. Insights from interviews with parents indicate that they employ role modeling, habituation, educational consequences, and rewards as strategies for instilling a thrifty lifestyle. Interviews with children provide information on parental practices such as reducing pocket money, setting examples of attitude and behavior, and limiting screen time. In conclusion, parents employ role modeling, habituation, educational consequences, and rewards to instill a thrifty lifestyle in their children.